EFFECTS OF THE APPLICATION OF RESEARCH METHODS IN THE LESSONS OF MATHEMATICS IN THE PRIMARY SCHOOL (Scientific journal of the Fergana State University, 2023)
This article describes some methods of teaching mathematics in elementary grades and their application. The importance of research methods in solving problems and assignments is revealed. Today, primary school students are thinking about the tasks that need to be completed in mathematical education, and about ways to solve them.